Comparative Analysis of HIRARC and HIRADC Methods in Occupational Safety Risk Management for Girder Erection Projects - Edo Dinata; Krisna Septian Pramayogi; Aniessa Rinny Asnanning; Agustina, Resti (WISE Pendidikan Indonesia, 2025)
This research investigates the integration of Occupational Health and Safety Management Systems (OHSMS) into girder erection activities within a major infrastructure development, emphasizing a comparison between two risk assessment approaches: HIRARC (Hazard Identification, Risk Assessment, and Risk Control) and HIRADC (Hazard Identification, Risk Assessment, and Determining Control). The objective is to assess which method offers more precise and actionable guidance for hazard mitigation in the context of heavy structural lifting. A qualitative case study was conducted at the Kayu Agung–Palembang–Betung toll road project in Indonesia. Field-based data collection included direct observations, documentation review, and stakeholder interviews. Each method was applied to systematically identify occupational hazards, evaluate their potential impacts, and formulate appropriate control strategies. Further analysis was performed to determine the safety factor of 180-ton and 250-ton cranes involved in the girder installation. A projected cost for OHSMS implementation was also calculated. The study reveals that HIRADC delivers clearer control recommendations and more targeted risk prioritization compared to HIRARC, making it better suited for high-risk construction scenarios. The larger crane, with a safety factor of 1.89, proved more reliable than the 180-ton model (1.65). The total cost required to implement comprehensive safety procedures was estimated at IDR 159,435,000. Critical risks identified include girder drops, worker falls from height, and contact with moving equipment. The insights gained from this study can enhance occupational safety planning and serve as a reference for similar engineering projects in emerging economies.